Community study of knowledge of and attitude to mental illness in Nigeria (2005)
Background: The improvement of community tolerance of people with Mental illness is important for their integration. Little is known about the knowledge of and attitude to mental illness in sub-Saharan Africa. Aims: To determine the knowledge and attitudes of a representative community sample in Nigeria. Method: A multistage, clustered sample of household respondents was studied in three states in the Yoruba-speaking parts of Nigeria (representing 22% of the national population). A total of 2040 individuals participated (response rate 74.2%). Results: Poor knowledge of causation was common. Negative views of mental illness were wide spread, with as many as 96.5% (s.d. =0.5) believing that people with mental illness are dangerous because of their violent behaviour. Most would not tolerate even basic social contacts with a mentally ill person: 82.7% (s.e.=1.3) would be afraid to have a conversation with a mentally ill person and only16.9% (s.e.=0.9) would consider marrying one. Socio-demographic predictors of both poor knowledge and intolerant attitude were generally very few. Conclusions: There is widespread stigmatisation of mental illness in the Nigerian community. Negative attitudes to mental illness may be fuelled by notions of causation that suggest that affected people are in some way responsible for their illness, and by fear.